1994
DOI: 10.1111/j.1365-2141.1994.tb06745.x
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐year survival and prognostic factors in multiple myeloma

Abstract: Among 1119 Japanese patients with symptomatic multiple myeloma diagnosed between 1965 and 1981, 38 (3.4%) survived more than 10 years. Younger age, low tumour mass (absence of severe anaemia, hypercalcaemia, renal failure, and multiple bone lesions), low plasma cell percentage in bone marrow, mature and intermediate myeloma according to Greipp's criteria, and a positive response to subsequent treatment, were related to long-term survival according to univariate analysis. Multivariate logistic regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 9 publications
2
23
1
Order By: Relevance
“…The literature, however, is by no means devoid of instances of 10-year survival following conventional chemotherapy [11][12][13][14][15][16][17]. This points to the existence of a possibly "low-risk" subset of patients whose unexpectedly long survival is due to largely unknown reasons.…”
Section: Introductionmentioning
confidence: 86%
“…The literature, however, is by no means devoid of instances of 10-year survival following conventional chemotherapy [11][12][13][14][15][16][17]. This points to the existence of a possibly "low-risk" subset of patients whose unexpectedly long survival is due to largely unknown reasons.…”
Section: Introductionmentioning
confidence: 86%
“…PC of these patients were divided into 4 subtypes (mature, intermediate, immature and plasmoblasts). The most extensive clinical study from that time period is the Japanese study of 1119 patients published in 1994 [8]. Patients who survived for more than 10 years had more mature plasmocytes in BM biopsies when compared to patients with shorter survival (54% vs. 31%; p= 0,01).…”
Section: Discussionmentioning
confidence: 99%
“…Overall survival (OS) was found to be 54 months for patients with plasmoblasts < 2% in comparison to 20 months for patients with plasmoblasts ≥ 2% [5]. In the largest morphological study conducted in Japan on 1119 patients, the presence of more mature plasmocytes also showed better prognosis [8].…”
mentioning
confidence: 99%
“…As a few previously reported cases of multiple myeloma with prolonged disease-free survival, this patient has been in CR for more than 10 years, and her disease condition represents ‘a cure’ or ‘a state extremely close to cure’ [14, 15, 16, 17]. Many investigators have suggested prognostic factors of multiple myeloma [5, 6, 9, 18]. This patient had some favorable prognostic factors: a relatively young age, a normal platelet count and normal serum creatinine, serum calcium, serum β 2 -M and CRP levels, a favorable M-protein type and a favorable morphological type of myeloma [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite these therapies, few cases have been considered to be cured [3]. Conventional chemotherapy has led to prolonged survival (over 10 years) in only about 2–4% of patients, with many of these patients exhibiting signs suggesting the presence of tumors, and very few cases in which an uneventful cure is expected [5, 6, 7]. …”
Section: Introductionmentioning
confidence: 99%